Protection against Radiotherapy-Induced Toxicity - Susan Hall; Santosh Rudrawar; Matthew Zunk; Nijole Bernaitis; Devinder Arora; Catherine M McDermott; Shailendra Anoopkumar-Dukie (MDPI AG, 2016)
Radiation therapy is a highly utilized therapy in the treatment of malignancies with up to 60% of cancer patients receiving radiation therapy as a part of their treatment regimen. Radiation therapy does, however, cause a wide range of adverse effects that can be severe and cause permanent damage to the patient. In an attempt to minimize these effects, a small number of compounds have been identified and are in use clinically for the prevention and treatment of radiation associated toxicities. Furthermore, there are a number of emerging therapies being developed for use as agents that protect against radiation-induced toxicities. The aim of this review was to evaluate and summarise the evidence that exists for both the known radioprotectant agents and the agents that show promise as future radioprotectant agents.